Mechanisms underlying alterations in glucose metabolism due to exercise - Mayumi Takagi; Yasuko Manabe (Japanese Society of Physical Fitness and Sports Medicine, 2014)
Exercise is known to affect glucose metabolism in healthy and diabetic individuals. Recent studies have demonstrated that both acute and chronic exercise improve glucose metabolism via several mechanisms. Acute exercise increases glucose uptake through activation of AMP-activated protein kinase with an increase in the intracellular AMP/ATP ratio, and also increases insulin sensitivity, possibly through TBC1 domain family member 4 regulation in the post-exercise period. Exercise also affects other organs in addition to skeletal muscle. Chronic exercise affects insulin secretion from the pancreas in response to glucose stimulation. This review describes how acute or chronic exercise regulates glucose metabolism. Although the detailed mechanisms remain unclear, these pathways might explain why exercise improves whole-body glucose metabolism.